answersLogoWhite

0


Best Answer

cot2x-tan2x=(cot x -tan x)(cot x + tan x) =0

so either cot x - tan x = 0 or cot x + tan x =0

1) cot x = tan x => 1 / tan x = tan x => tan2x = 1 => tan x = 1 ou tan x = -1

x = pi/4 or x = -pi /4

2) cot x + tan x =0 => 1 / tan x = -tan x => tan2x = -1

if you know about complex number then infinity is the solution to this equation, if not there's no solution in real numbers.

User Avatar

Wiki User

โˆ™ 2011-05-18 19:26:57
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is the answer to cot squared x - tan squared x equals 0?
Write your answer...
Submit
Related questions

How do you make the left the same as the right for tan 0 times cot 0 all over tan 0 csc2 0?

You cannot because cot(0) is not defined, neither is cosec(0).


What is wrong with the following statement tan 90 degrees equals 1 overcot 90 degrees?

Cot(90) = 0 so 1/cot(90), if defined, would be 1/0. Such a fraction is not defined and that is what is wrong with the sentence.


What is the solution to cos tan-sin over cot equals 0?

either cos OR tan-sin equals zero socos=0 at pi/2 and 3pi/2ortan=sin which is impossibleim not sure though


What is tan of 0?

Tan of 0 equals zero.


What is the exact trigonometric function value of cot 0?

There is no value cot 0, because cot 0 is equivalent to 1 / tan 0, which is equivalent to 1 / 0, which is undefined. That said, the limit of cot x as x approaches 0 is infinity.


If tansqtheta plus 5tantheta0 find the value of tantheta plus cottheta?

tan2(theta) + 5*tan(theta) = 0 => tan(theta)*[tan(theta) + 5] = 0=> tan(theta) = 0 or tan(theta) = -5If tan(theta) = 0 then tan(theta) + cot(theta) is not defined.If tan(theta) = -5 then tan(theta) + cot(theta) = -5 - 1/5 = -5.2


What is 0 squared?

0 squared is 0. Zero times zero equals zero.


What does 0 squared equal?

It equals 0. Zero times zero equals zero.


How do you factor x squared -2x-3 equals 0?

x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0


How do you solve tan squared theta - tan theta equals 0?

Let x = theta, since it's easier to type, and is essentially the same variable. Since tan^2(x)=tan(x), you know that tan(x) must either be 1 or zero for this statement to be true. So let tan(x)=0, and solve on your calculator by taking the inverse. Similarly for, tan(x)=1


What are the 6 trig functions for 0 degrees 90 degrees 180 degrees 270 degrees?

sin(0) = 0, sin(90) = 1, sin(180) = 0, sin (270) = -1 cos(0) = 1, cos(90) = 0, cos(180) = -1, cos (270) = 0 tan(0) = 0, tan (180) = 0. cosec(90) = 1, cosec(270) = -1 sec(0) = 1, sec(180) = -1 cot(90)= 0, cot(270) = 0 The rest of them: tan(90), tan (270) cosec(0), cosec(180) sec(90), sec(270) cot(0), cot(180) are not defined since they entail division by zero.


How do you solve 16t squared minus 9 equals 0?

Solve this problem -x squared -40x- 80 =0


What is 3x squared plus 6x-3 equals 8 in the form of Ax squared plus Bx plus C equals 0?

It is: 3x2+6x-11 = 0


Does cos squared x over sin squared x equal cot squared x?

Yes. Except where sin x = 0, because then you would be dividing by zero so the quotient is undefined.


How do you solve x squared minus 10 equals 0?

If x squared -10 = 0 then x = the square root of 10


What is the answer to 7x squared plus 2x equals 0?

63828


True or false the solution of the equation of x squared plus 4x equals 0 is identical to the solution of 3x squared plus 12x equals 0?

True because in both equations x = 0 or x = -4


What is the vertex when Y equals X squared - 3?

(0, -3)


What is the answer to 2x squared -2x -40 equals 0 is it x equals 5 and x equals -4?

Yes it is and well done.


Is x squared plus 7x-30 equals 0 a linear equation?

No, It's a a quadratic equation because you have X squared.


What are the values of x and y when x minus y equals 0 and x squared plus y squared equals 18?

(x, y) = (-3, -3) or (3, 3)


How do you factor 16y squared - 8y equals 0?

16y2-8y=0 8y(2y-1)=0


Does 0 squared equal 1?

No, it equals 0. If you have nothing, and you multiply it by nothing, you still have nothing.


Factor 2x squared - 6x plus 4 equals 0?

(2x-4)(x-1) = 0


Factor x squared - 8x plus 15 equals 0?

(x-3)(x-5) = 0

Study guides

๐Ÿ““
Create a Study Guide